2022
DOI: 10.1002/jbio.202200218
|View full text |Cite
|
Sign up to set email alerts
|

Theranostic‐guided corneal cross‐linking: Preclinical evidence on a new treatment paradigm for keratoconus

Abstract: Theranostics is an emerging therapeutic paradigm of personalized medicine; the term refers to the simultaneous integration of therapy and diagnostics. In this work, theranostic‐guided corneal cross‐linking was performed on 10 human sclero‐corneal tissues. The samples were soaked with 0.22% riboflavin formulation and underwent 9 minutes UV‐A irradiance at 10 mW/cm2 using theranostic device, which provided both a measure of corneal riboflavin concentration and a theranostic score estimating treatment efficacy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…The results from the epi-off protocol were in strict agreement with previous work, thus confirming the theranostic-guided CXL procedure reproducibility. 17 In addition, they were in agreement with previous reports showing, in the 3 to 10 mW/cm 2 range of power densities for 5.4 J/cm 2 energy dose, that UV-A light-mediated photodegradation of riboflavin in the corneal stroma is only energy-dependent in accordance with the Bunsen-Roscoe law and that the transepithelial irradiation with 10 mW/cm 2 for 9 minutes is effective in photodegrading intrastromal riboflavin as the conventional direct stromal irradiation by 3 mW/cm 2 for 30 minutes. 11,[14][15][16][29][30][31] This evidence could not be extrapolated for UV-A power density or energy dose higher than 10 mW/cm 2 or 5.4 J/cm 2 , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results from the epi-off protocol were in strict agreement with previous work, thus confirming the theranostic-guided CXL procedure reproducibility. 17 In addition, they were in agreement with previous reports showing, in the 3 to 10 mW/cm 2 range of power densities for 5.4 J/cm 2 energy dose, that UV-A light-mediated photodegradation of riboflavin in the corneal stroma is only energy-dependent in accordance with the Bunsen-Roscoe law and that the transepithelial irradiation with 10 mW/cm 2 for 9 minutes is effective in photodegrading intrastromal riboflavin as the conventional direct stromal irradiation by 3 mW/cm 2 for 30 minutes. 11,[14][15][16][29][30][31] This evidence could not be extrapolated for UV-A power density or energy dose higher than 10 mW/cm 2 or 5.4 J/cm 2 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…34 The k c parameter represents the resistance to deformation under load and is a strain-dependent value that changes with strain (or corneal deformation). 17 It has been previously validated through analysis of several corneal conditions, including response to CXL treatment. 17,24,25,28,39,40 The authors have shown that during the air-puff event, due to the high loading magnitude (greater than 45 mm Hg) and fast rate (shorter than 20 milliseconds), the cornea is not able to undergo any viscous deformation; for this reason, a pure elastic material model, as performed in this study, could be selected for biomechanical modeling of cornea in dynamic tonometry tests because neglecting a corneal viscoelastic behavior has been shown not to significantly affect the results of the study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations